THE POTENTIAL FOR EDUCATION AND REHABILITATION IN A NEIGHBOURHOOD OFFICER’S SERVICE - Ernest Magda; Adam Stankiewicz (Probacja, 2025)
The police are commonly associated with implementing preventive and repressive measures against lawbreakers, the aim being to protect public order and security. In recent years, however, a new educational function has emerged within the socialised model of policing (Community Policing). This educational role target children and young people, as well asadult victims of crime, through the implementation of numerous crime prevention programmes. It also extends to adult offenders, taking the form of rehabilitative education. Within the structure of the Polish Police, neighbourhood police officers bear the primary responsibility for preventive and educational activities. This study analyses the legal acts that form the basis for the use of educational measures by police officers. It then draws on open-ended, in-depth interviews conducted with neighbourhood officers. The findings allowed us to formulate a preliminary hypothesis: that the educational impact of neighbourhood police officers is determined more by the personal characteristics of offenders, such as age or socio-economic background, than by the nature of their crime. Furthermore, the age and years of service as a neighbourhood police officer affect their willingness to use educational rather than repressive measures.